New national and regional Annex I Habitat records: from #123 to #138 - Rivieccio, Giovanni; Bagella, Simonetta; Bazan, Giuseppe; Bonari, Gianmaria; Brunco, Vanessa; Buffa, Gabriella; Candini, Francesco; Cannucci, Silvia; Caria, Maria Carmela; Ciaschetti, Giampiero; De Simone, Leopoldo; Di Pietro, Adriano; et al. (Plant Sociology, 2024)
New Italian data on the distribution of some of the Annex I Habitats are reported in this contribution. Specifically, 16 records are presented including 9 new occurrences in Natura 2000 sites, and 27 new cells are added in the EEA 10 km × 10 km reference grid. The new data refer to the Italian administrative regions of Abruzzo, Apulia, Latium, Marche, Lombardy, Piedmont, Sardinia, Sicily, Tuscany, and Veneto.